A framework for semiconductor industry supply chain planning: perspectives of intelligent enterprise. (1st January 2012) - Bahinipati, Bikram K.
Supply chain planning in the semiconductor industry integrates the complex network of wafer foundries, probe and assembly manufacturing sites together to enhance operational effectiveness. So, the supply chain planning system should aggregate data from multiple sources to provide visibility and interoperable collaboration to an extended network of stakeholders. While exploring buyer-supplier collaborative relationships and new procurement opportunities, the present work proposes the perspectives of business planning, supply management, demand management, multi-echelon inventory optimization, customer order fulfilment, and transportation and logistics management. The novelty of this work lies in the simultaneous consideration of six interrelated perspectives of supply chain planning along with the perspective of collaboration among supply chain enterprises on the basis of information sharing. The proposed framework captures the technological and business basis for integration of various elements for supply chain planning for cost-efficient intelligent enterprises.